Distribution of elements between copper and FeOx-CaO-SiO2 slags during pyrometallurgical processing of WEEE. (1st September 2013) - Anindya, A.; Swinbourne, D. R.; Reuter, M. A.; Matusewicz, R. W.
Abstract : The rapidly increasing rate of creation of electronic waste (WEEE) requires the development of effective processing strategies so that the valuable (minor) metals and compounds in WEEE can be kept within the materials cycle while the possibly harmful elements and compounds can be kept out of the environment. Pyrometallurgical processing currently offers the most attractive routes to perform the initial separation before the usual hydrometallurgical refining steps to produce high purity metals and compounds. There is a lack of information on the way valuable metals in WEEE behave during smelting because the combination of metals in WEEE is frequently different to that found in natural ores. In this first paper the slag/metal distribution ratio of tin between FeOx -CaO-SiO2 slags and copper was examined at an oxygen partial pressure of 10 −8 MPa (10 −7 atm) and at 1300°C. The distribution ratio of tin was unaffected by the Fe/SiO2 ratio of the slag, over the range examined, but strongly dependant on the CaO content. The higher the CaO content the smaller the slag/metal distribution ratio and, consequently, the greater the activity coefficient of SnO(l) in the slags. Iso-distribution ratio lines and iso-SnO(l) activity coefficient lines were presented on the copper-saturated FeOx -CaO-SiO2 phase diagram. Tin volatilisation during the converting stage of WEEE processing in a black copper smelter would be improved by using slag with a high CaO content for the given slag system. The distribution of indium, mostly found in liquid crystal displays, will be examined in a subsequent paper.